Anticancer properties of lipid and poly(ε‐caprolactone) nanocapsules loaded with ferrocenyl‐tamoxifen derivatives. (23rd August 2018) - Najlaoui, Feten; Pigeon, Pascal; Aroui, Sonia; Pezet, Mylène; Sancey, Lucie; Marrakchi, Naziha; Rhouma, Ali; Jaouen, Gérard; De Waard, Michel; Busser, Benoit; Gibaud, Stéphane
Abstract: Objective: We synthesized new tamoxifen derivatives as anticancer drug candidates and elaborated on convection‐enhanced delivery (CED) as a strategy for delivery. Methods: To overcome the issue of their poor solubility, these ferrocenyl‐tamoxifen derivatives were esterified and encapsulated into different nanocarriers, that is lipid (LNC) and polymeric nanocapsules (PNL‐NC). We describe the chemistry, the encapsulation and the physicochemical characterization of these formulations. Key findings: Starting compounds [phthalimido‐ferrocidiphenol and succinimido‐ferrocidiphenol], esterified prodrugs and their nanocapsules formulations were characterized. These drug candidates displayed a strong in vitro activity against breast and glioblastoma cancer cells. The ester prodrugs were toxic for glioblastoma cells (IC50 = 9.2 × 10 −2 μm and 6.7 × 10 −2 μm, respectively). The IC50 values for breast cancer cells were higher for these compounds. The encapsulation of the esterified compounds in LNCs (≈50 nm) or PCL‐NCs (≈300 nm) did not prevent their efficacy on glioblastoma cells. These anticancer effects were due to both blockade in the S‐phase of the cell cycle and apoptosis. Moreover, the tamoxifen derivatives‐loaded nanocapsules induced no toxicity for healthy astrocytes and showed no haemolytic properties. Loaded Lipid Nanocapsules (LNCs) presented interesting profiles for the optimal delivery of active compounds. Conclusions: Phthalimido‐ and Succinimido‐esters represent an innovative approach to treat cancers with cerebral localizations such as glioblastoma or brain metastases from breast cancers.